2022
DOI: 10.1155/2022/2566746
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Analysis of Liver Cirrhosis Patients with Cerebral Infarction and/or Gastrointestinal Hemorrhage: A Retrospective Cohort Study

Abstract: Background. To explore the risk factors of gastrointestinal hemorrhage and/or cerebral infarction complications in liver cirrhosis and provide evidence for early prevention, clinical diagnosis, and treatment of liver cirrhosis. Methods. 200 liver cirrhosis patients were analyzed: liver cirrhosis ( n = 78 ), liver cirrhosis complicated with cerebral infarction ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%